Risk Factors Associated with Disability among Elderly with Stroke in Indonesia: A Secondary Data Analysis of 2018 National Basic Health Research - Yanti, Anisa Dwi Lutfi; Santik, Yunita Dyah Puspita (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2022)
Introduction: According to the 2018 Basic Health Research (Riskesdas), the highest prevalence of stroke occurs among the elderly group. On the other hand, the proportion of disability among the elderly with stroke was highest compared to the elderly with another disease. Disabled elderly resulted in a high burden of care. This study aimed to analyze the risk factors associated with disability among the elderly with stroke in Indonesia.Methods: This cross-sectional study uses secondary data from Riskesdas 2018. The sample was all elderly aged ≥60 years in Indonesia that participated in the Riskesdas 2018 who diagnosed with stroke by a doctor and met the inclusion criteria (2439 samples). This study employed chi-square and logistic regression.Results: The risk factors associated with disability among the elderly with stroke were older age, having a low education level, living in a rural area, not being obese, having a mental emotional disorder, having no smoking history, and less physical activity. Multivariate analysis showed that less physical activity (PR=18.097; 95%CI=7.306-44.825), low level of education (PR=3.555; 95%CI=1.616-7.823), mental emotional disorders (PR=1.942; 95%CI=1.262-2.988) were the risk factors of disability among elderly with stroke. Being obese (PR= 0.578; 95%CI=0.345-0.970), having a joint disease (PR=0.546; 95%CI=0.311-0.958), and having a smoking history (PR=0.461; 95%CI=0.280-0.759) were the protective factors of disability among elderly with stroke.Conclusion: Physical rehabilitation and mental-emotional disorder treatment have important roles in preventing disability among the elderly with stroke